KADAR FORMALIN PADA IKAN ASIN DENGAN MENGGUNAKAN SPEKTROFOTOMETER PADA PEDAGANG IKAN ASIN DI PASAR TRADISIONAL KOTA SIBOLGA TAHUN 2018 - HERLINA . (JURNAL ILMIAH KOHESI, 2019)
Formalin is the commercial name of formaldehyde compounds with levels of 35–40% in water. Formalin is a group of strong disenfektan compounds that are often used as preservative bodies, but food preservatives can also be used, although formalin is not permitted for food preservatives and additional ingredients. This study aims to detect formalin contained in salted fish in the Sibolga City Market. The spectrophotometric method was used in this study, which was measured at a wavelength of 400 nm. Based on the results obtained from 10 samples of salted fish analyzed, taken from two traditional markets, namely the selasa market or Panam market and the Arengka morning market, and from this study, there were 2 salted fish detected containing formaldehyde, which was bloated salted fish with formalin concentration 18.71 ppm and salted petek fish of 22.88 ppm.